Chemical epidural abscess: case report. Issue 3 (June 1971) - Vijayan, N.; Dreyfus, P. M.
Abstract : Spinal epidural abscess accompanies blood-borne infection, vertebral osteomyelitis, or an overlying cutaneous source of infection. This report documents the development of non-infective epidural abscess where the inflammatory response was induced by the highly irritant contents (keratin and cholesterol) of an underlying epidermoid. This was associated with aseptic meningitis.